Behavior of auxetic structures under compression and impact forces - Yang, Chulho; Vora, Hitesh D; Chang, Young (Smart materials and structures, 2018)
In recent years, various auxetic material structures have been designed and fabricated for diverse applications that utilize normal materials that follow Hooke's law but still show the properties of negative Poisson's ratios (NPR). One potential application is body protection pads that are comfortable to wear and effective in protecting body parts by reducing impact force and preventing injuries in high-risk individuals such as elderly people, industrial workers, law enforcement and military personnel, and athletes. This paper reports an integrated theoretical, computational, and experimental investigation conducted for typical auxetic materials that exhibit NPR properties. Parametric 3D CAD models of auxetic structures such as re-entrant hexagonal cells and arrowheads were developed. Then, key structural characteristics of protection pads were evaluated through static analyses of FEA models. Finally, impact analyses were conducted through dynamic simulations of FEA models to validate the results obtained from the static analyses. Efforts were also made to relate the individual and/or combined effect of auxetic structures and materials to the overall stiffness and shock-absorption performance of the protection pads. An advanced additive manufacturing (3D printing) technique was used to build prototypes of the auxetic structures. Three different materials typically used for fused deposition modeling technology, namely polylactic acid (PLA) and thermoplastic polyurethane material (NinjaFlex and SemiFlex ), were used for different stiffness and shock-absorption properties. The 3D printed prototypes were then tested and the results were compared to the computational predictions. The results showed that the auxetic material could be effective in reducing the shock forces. Each structure and material combination demonstrated unique structural properties such as stiffness, Poisson's ratio, and efficiency in shock absorption. Auxetic structures showed better shock absorption performance than non-auxetic ones. The mechanism for ideal input force distribution or shunting could be suggested for designing protectors using various shapes, thicknesses, and materials of auxetic materials to reduce the risk of injury.